Chronic endometritis in women with suspected retained products of conception and their reproductive outcomes. (13th March 2021) - Elder, Simone; Bortoletto, Pietro; Romanski, Phillip A.; Spandorfer, Steven
Abstract: Objective: To determine whether women who underwent operative hysteroscopy for suspected retained products of conception (rPOC) have histopathologic evidence of chronic endometritis (CE). Design: Retrospective cohort. Setting: Academic center. Patient(s): One hundred and eleven women who underwent operative hysteroscopy for suspected rPOC between 2016 and 2018. Intervention(s): None. Main Outcome Measure(s): Evidence of CE on histopathology and subsequent reproductive outcomes. Result(s): One hundred and eleven women with retained products of conception were included in our study of which 26 (23.4%) were diagnosed with CE. Women without CE had a higher median gravidity (1 vs. 2, p  = .021) and a higher median number of prior pregnancy losses (1 vs. 2 prior losses, p  = .005) compared to those with CE. Subsequent pregnancy data were available for 63 women. There was no difference in the subsequent pregnancy rate (61.5 vs. 54%, p  = .626) between those with and without CE. Once pregnant, miscarriage (37.5 vs. 25.9%, p  = .524) and live birth rates (50 vs. 44.4%, p  = .782) were similar between the groups. Women with CE received antibiotics 57.7% of the time, the most common of which was doxycycline (46.6%). Of the women with CE who received antibiotics ( n  = 10), 8 became pregnant, and 4 of whom went on to have a live birth. Conclusion(s): Nearly 1 in 4 women undergoing hysteroscopy for rPOC was incidentally diagnosed with CE. It is not clear whether CE is a causative agent for retained products or a response to the pregnancy loss. In this cohort, a diagnosis of CE did not negatively impact subsequent reproductive outcomes.